Turistas - Stockwell, John.; Ross, Michael Arlen; Twentieth Century Fox.; Fox Atomic; 2929 Production; Stone Village Pictures; BoZ Productions (United States of America Twentieth Century Fox ; distributed in the Philippines by Viva Video, 2006)
After a terrifying bus accident maroons a diverse group of young adventure travelers in a remote Brazilian beach town, they slowly discover that the white sand beaches and lush jungles are concealing a darker, unsettling secret.
Editor, Jeff McEvoy ; music supervisor, David Falzone ; music, Paul Haslinger.
Josh Duhamel, Melisaa George, Olivia Eilde, Desmond Askew, Beau Garrett, Max Brown, Agles Steib, Miguel Linardi.
VCD
Keywords: Drama; Thriller; Mystery